Characterisation of in-situ reactive plasma-sprayed nano-(Ti, V)N composite ceramic coatings with various V concentrations. Issue 8 (15th April 2021) - Lv, Yilin; Chi, YunLong; Mao, XinYe; Xue, MingMing; Dong, Yanchun; Yang, Yong; He, JiNing
Abstract: The effect of V concentration on the microstructure and phase composition of nano-(Ti, V)N composite ceramic coatings prepared by in-situ reactive plasma spraying of mechanically mixed Ti–V powders were investigated using X-ray diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, X-ray energy dispersive spectroscopy, and transmission electron microscopy. The microhardness, toughness, wear resistance, and strengthening mechanism of the prepared nano-(Ti, V)N coatings were measured and analysed. The results showed that the nano-(Ti, V)N coating comprised a large proportion of nano-(Ti, V)N grains, which was the solid solution of TiN and VN. All the V atoms completely entered the TiN lattice and the solubility limit of V in TiN is approximately 25 wt%. The grains of the (Ti, V)N (25 wt% V) coating had a face-centred cubic structure and a large quantity of twins; they were primarily equiaxed grains morphology with a few columnar grains. From comparing the experimental statistics, the (Ti, V)N (25 wt% V) coating displayed the highest microhardness (1952 ± 78.5 Hv) and the most even dispersion but a slightly lower toughness compared with the (Ti, V)N (35 wt% V) coating. The (Ti, V)N (25 wt% V) coating with a dense microstructure obtained a high microhardness due to dislocation strengthening, fine grain strengthening, and solid solution strengthening (from the solid solution of VN in TiN). Furthermore, a lower friction coefficient and wear volume loss indicated that the (Ti, V)N (25 wt% V) coating had superior tribological properties and great potential as a wear resistant coating.